Beyond infertility: user’s narratives on assisted reproduction in Córdoba, Argentina - Johnson, María Cecilia (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2021)
This article presents the results of gender-focused doctoral research about the experience of Argentine women with Assisted Reproduction Techniques (ARTs). In Argentina, the current law regulating access to ARTs guarantees access to a variety of users who do not always start from an infertility diagnosis. The main objective is to know the different relationships of the users with reproductive technology. From a feminist perspective, the study is based on the qualitative analysis of ARTs users’ narratives, by coding them. As result, two broad categories are identified: “repair stories”, where the decision to use the TRHA is linked to the notion of infertility, and the so-called “simultaneity stories” where reproductive technology appears enabling a reproductive choice. These reflections are a contribution to discuss the technologies from the user's experiences, as well as the tensions in the construction of reproductive autonomy.